Molecular mechanisms of the influenza fusion peptide: insights from experimental and simulation studies - Diana Lousa (Wiley, 2021)
A key step in infections by enveloped viruses, such as influenza, is the fusion between the viral envelope and the host cell membrane, which allows the virus to insert its genetic material into the host cell and replicate. The influenza virus fusion process is promoted by hemagglutinin (HA), a glycoprotein that contains three identical monomers composed of two polypeptide chains (HA1 and HA2). Early studies on this protein revealed that HA‐mediated fusion involves the insertion of the HA2 N‐terminal segment into the host membrane and that this segment, known as the fusion peptide, is a key player in the fusion process. This mini‐review highlights the main findings that have been obtained by experimental and computational studies on the HA fusion peptide, which give us a glimpse of its mode of action.